Ancient concepts of the Hippocratic : papers presented at the XIIIth International Hippocrates Colloquium, Austin, Texas, August 2008 - Dean-Jones, Lesley; Rosen, Ralph Mark (Studies in ancient medicine ;, 2016)
In Ancient Concepts of the Hippocratic, Lesley Dean-Jones and Ralph Rosen have gathered 19 international authorities in ancient medicine to identify commonalities among the treatises of the Hippocratic Corpus which led scholars of antiquity to group them under the single name of Hippocrates. Most recent scholarship has drawn attention to the divergences between individual treatises and groups of treatises, emphasizing the agonistic facet of the ancient medical profession. In contrast, in this volume contributors look to find points of agreement between the writings that go beyond claims of rationality. Topics considered include ontological claims about the discipline of medicine itself, the view of the patient as a perceiving unity, theories on the function of glands and the importance of regimen.